Voluntary language switching: When and why do bilinguals switch between their languages? - de Bruin, Angela; Samuel, Arthur G.; Duñabeitia, Jon Andoni (Journal of memory and language, 2018)
•We examined when and why bilinguals switch voluntarily between languages.•Language choice and language switching were related to lexical access.•The voluntary and cued task showed longer RTs for switch than non-switch trials.•In the cued task, using two languages was more costly than using one (mixing cost).•In the voluntary task, using two languages was faster than one (mixing benefit). Bilingual language switching has been studied extensively in cued picture naming paradigms, instructing bilinguals when to switch between languages. However, in daily life, bilinguals often switch freely, without external instruction. This study examined when and why bilinguals switch voluntarily. Spanish-Basque bilinguals frequently switched between their languages and their language choice was related to the ease of lexical access. Words that were slow to be accessed in Basque were more often named in Spanish and vice versa. In terms of response times, switching costs were observed not only in the cued but also in the voluntary task. However, while cued switching showed a mixing cost (reflecting the cost associated with using two languages rather than one), a mixing benefit was observed for the voluntary task. This suggests that voluntarily using two languages may be less costly than having to stay in one language.